1987
DOI: 10.1159/000149710
|View full text |Cite
|
Sign up to set email alerts
|

A New Family of Vertebrate Viruses: <i>Toroviridae</i>

Abstract: The proposed family Toroviridae is characterized by eveloped, peplomer-bearing particles containing an elongated tubular nucleocapsid with helical symmetry. The capsid may bend into an open torus, conferring a biconcave disk or kidney-shaped morphology to the virion (largest diameter 120–140 nm) or the capsid may be straight, resulting in a rod-shaped particle (35 × 170 nm). Morphogenesis is by budding of preformed nucleocapsids through membranes mainly of the Golgi system and of the rough endoplasmic reticulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 11 publications
0
34
0
Order By: Relevance
“…Snijder and M. C. Horzinek (c) and the physicochemical properties of BEV (Weiss & Horzinek, 1986a) led to the proposal of a new family of enveloped animal viruses, the Toroviridae Horzinek et al, 1987;; BEV, the only torovirus so far which can be grown in cultured cells, was identified as the prototype.…”
Section: History Of Torovirologymentioning
confidence: 99%
See 1 more Smart Citation
“…Snijder and M. C. Horzinek (c) and the physicochemical properties of BEV (Weiss & Horzinek, 1986a) led to the proposal of a new family of enveloped animal viruses, the Toroviridae Horzinek et al, 1987;; BEV, the only torovirus so far which can be grown in cultured cells, was identified as the prototype.…”
Section: History Of Torovirologymentioning
confidence: 99%
“…Based on their morphological and physicochemical characteristics, the Toroviridae were initially proposed to constitute a new family of enveloped RNA viruses Horzinek et al, 1987). However, recent analysis of the genetic information and replication strategy of the prototype Berne virus (BEV) (Snijder et al, 1988(Snijder et al, , 1990a has revealed that toroviruses are not unique: they are clearly related to the Coronaviridae and, more distantly, to the arteriviruses (den Boon et al, 1991 b).…”
Section: General Introductionmentioning
confidence: 99%
“…Berne virus (BEV) of horses is a representative of a recently defined group of vertebrate RNA viruses, for which the family status and the name Toroviridae have been proposed Horzinek et al, 1987); antigenically related toroviruses have been demonstrated in cattle (Woode et al, 1985) and humans (Beards et al, 1984). The present state of knowledge regarding the toroviruses has been reviewed recently (Weiss & Horzinek, 1987;Horzinek et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…The present state of knowledge regarding the toroviruses has been reviewed recently (Weiss & Horzinek, 1987;Horzinek et al, 1987). The equine isolate BEV is the best studied member of the proposed family, since it is the only torovirus so far that can be propagated in cultured cells.…”
Section: Introductionmentioning
confidence: 99%
“…Berne virus (BEV) is the type species of a group of enveloped positive-strand RNA viruses, the toroviruses (Horzinek & Weiss, 1984;Horzinek et al, 1987), which has recently been recognized (by the International Committee on Taxonomy of Viruses) as 'a new genus with possible affinities to the coronavirus family'. During the past 4 years, analysis of the BEV genome structure and replication strategy has revealed that toroviruses are evolutionarily related to coronaviruses.…”
Section: Introductionmentioning
confidence: 99%